Congenital Pouch Colon: A Preliminary Report from Pakistan - Bilal Mirza; Sarfraz Ahmad; Afzal Sheikh (EL-Med-Pub, 2012)
Background: Congenital pouch colon (CPC) is a rare entity in patients of anorectal malformations (ARM) requiring special consideration as to the management. This study is aimed at evaluating the presentation, management, and the outcome of initial surgery in patients with CPC. Materials & Methods: This retrospective study was conducted in the department of Pediatric Surgery of our institute during May 2007- May 2010. The Information about the demography, clinical features, investigations, management, and the outcome of initial surgery was retrieved and analyzed. Results: There were 21 patients of CPC managed during the study period. Sixteen (76%) were males and five (24%) females (M:F 3.2:1). Mean age of presentation was 4.8 days with a range of 12 hours to 45 days. In 18 (85.7%) patients, CPC was found with high ARMs, whereas, in 3 (14.3%) patients it was associated with low ARMs. Imperforate anus with moderate to massive abdominal distension was the presentation in 16 (76%) patients. Abdominal radiographs helped in preoperative diagnosis in 8 patients. Two patients had pneumoperitoneum on abdominal radiographs. At operation, type I CPC was found in 9 (42.8%) patients, type II in 5 (23.8%), type III in 2 (9.5%) patients, and type IV CPC in 5 (23.8%) patients. In 11 (52.4%) patients, pouch was emptied and retained with proximal enterostomy. In 7 (33.3%) patients, end enterostomy with pouch excision was done. In two patients, a window colostomy was formed. In one patient, pouch was disconnected from the normal bowel and Hartmann's pouch with end ileostomy was formed. There were 2 (9.5%) deaths in our series.Conclusion: CPC is a rare malformation. Massive abdominal distension with imperforate anus is the common presentation. Optimum management can reduce the morbidity and mortality.